Design of Aromatic Ring-Based Polyphosphonium Salts Synthesized via ROMP and the Investigation into Their Antibacterial and Hemolytic Activities - Kuday, Hilal; Suer, N. Ceren; Bayir, Ali; Aksu, Burak; Hatipoglu, Arzu; Guncu, Mehmet Mucahit; Degitz, Ilayda Acaroglu; Gallei, Markus; Eren, Tarik (AMER CHEMICAL SOC, 2021)
In this study, phosphonium salt-bearing polynorbornenes were synthesized using five different aromatic side chains (triphenylphosphonium, trifluorophenyl phosphonium, trichlorophenyl phosphonium, tri(p-tolyl)phosphonium, and cyclohexyldiphenyl phosphonium) via ring-opening metathesis polymerization (ROMP). The biological activities of these polymers were determined by their minimal inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against Escherichia coli and Staphylococcus aureus, and additionally, cytotoxicity studies on red blood cells were performed to report on their hemolytic activities (HC50). All of the synthesized polymers were found to be more active toward S. aureus than E. coli, and among them, tri(p-tolyl)phosphonium-and cyclohexyldiphenyl phosphonium-bearing homopolymers were found to be the most active against S. aureus (MIC: 2 mu g mL(-1)) under the Mueller Hinton Broth (MHB) medium; however, the polymers were also found to be hemolytic (HC50 <= 8 mu g mL(-1)). The electron densities of the monomers were calculated via computational studies to investigate the structure-property relationship for the biocidal activities of polymers. Furthermore, the morphological changes of the bacteria in the presence of the polymers were investigated by scanning electron microscopy (SEM) and zeta potential studies using dynamic light scattering (DLS) to speculate about the killing mechanism of the biocidal polymers. In the second part of this study, a series of copolymers were also synthesized to obtain selective copolymers, i.e., nontoxic and biocidal polymers. Using proper monomer compositions in copolymer series, the selectivity against S. aureus versus human red blood cells was determined to be 128.
Keywords: ROMP; structure-property relationship; phosphonium; biocidal; antibacterial; OPENING METATHESIS POLYMERIZATION; ANTIMICROBIAL POLYMERS; CATIONIC BIOCIDES; PHOSPHONIUM SALTS; BLOCK-COPOLYMERS; MIMICS; Materials Science; Polymer Science